Allelic heterogeneity and abnormal vesicle recycling in PLAA-related neurodevelopmental disorders - Iacomino, Michele; Houerbi, Nadia; Fortuna, Sara; Howe, Jennifer; Li, Shan; Scorrano, Giovanna; Riva, Antonella; Cheng, Kai-Wen; Steiman, Mandy; Peltekova, Iskra; Yusuf, Afiqah; Baldassari, Simona; et al. (Frontiers in Molecular Neuroscience, 2024)
The human PLAA gene encodes Phospholipase-A2-Activating-Protein (PLAA) involved in trafficking of membrane proteins. Through its PUL domain (PLAP, Ufd3p, and Lub1p), PLAA interacts with p97/VCP modulating synaptic vesicles recycling. Although few families carrying biallelic PLAA variants were reported with progressive neurodegeneration, consequences of monoallelic PLAA variants have not been elucidated. Using exome or genome sequencing we identified PLAA de-novo missense variants, affecting conserved residues within the PUL domain, in children affected with neurodevelopmental disorders (NDDs), including psychomotor regression, intellectual disability (ID) and autism spectrum disorders (ASDs). Computational and in-vitro studies of the identified variants revealed abnormal chain arrangements at C-terminal and reduced PLAA-p97/VCP interaction, respectively. These findings expand both allelic and phenotypic heterogeneity associated to PLAA-related neurological disorders, highlighting perturbed vesicle recycling as a potential disease mechanism in NDDs due to genetic defects of PLAA.